Development of an online Irish food composition database for nutrients - Black, Lucinda; Ireland, J.; Møller, A.; Roe, M.; Walton, J.; Flynn, A.; Finglas, P.; Kiely, M. (Academic Press, 2011)
Food composition databases underpin national dietary surveys, support epidemiological and experimental research in human nutrition and are essential in the development of food regulations and dietary guidelines. To date, nutrition researchers in Ireland have not had access to national food composition data and have relied heavily on borrowed data—mainly from the United Kingdom. The aim of this project was to compile an on-line Irish food composition database, which is compatible with international standards. Data on foods specific to the Irish population, including commonly consumed manufactured products, composite dishes and nutritional supplements, were collected between 1997 and 2006 during national dietary intake surveys. In conjunction with EuroFIR (European Food Information Resource Network of Excellence), these foods have been compiled using standardised methodology. The database comprises 938 foods, with values for 41 components. Values for packaged products were sourced from manufacturers and values for composite dishes were calculated from ingredients. Homemade meat, fish and vegetable dishes, manufactured cereal products and nutritional supplements are the key foods in the database. The Irish food composition database is available on-line (http://www.ucc.ie/en/ifcdb) and is incorporated in the EuroFIR eSearch facility (http://www.eurofir.eu) alongside other European national and specialised food composition databases.